Effect of Defects on Strain Relaxation in InGaN/AlGaN Multiple‐Quantum‐Well Near‐Ultraviolet Light‐Emitting Diodes. Issue 2 (19th November 2021) - Islam, Abu Bashar Mohammad Hamidul; Shim, Jong-In; Shin, Dong-Soo; Kwak, Joon Seop
Abstract : Three similar‐structure InGaN/AlGaN multiple‐quantum‐well near‐ultraviolet (NUV) light‐emitting diodes (LEDs) are utilized to investigate the microscopic effect of defects on strain relaxation. Consistent correlations among the crystal quality, the piezoelectric field ( F PZ ), the internal quantum efficiency (IQE), and the bandgap shrinkage of NUV LEDs are obtained by investigating the macroscopic characterizations. The difference in crystal quality (or the defect density) of NUV LEDs is found by the ideality factor, the emission microscope image, the Shockley–Read–Hall coefficient, and the IQE. Electroreflectance spectra are used to calculate F PZ of NUV LEDs. F PZ, the IQE, and the peak‐wavelength shift at driving currents are increased with the samples' crystal quality compared to the reference sample. Also, F PZ, the IQE, and the peak‐wavelength shift are decreased with the increase in samples' defect densities. A similar result is found for the bandgap shrinkage. This effect significantly indicates that the strain relaxation is induced by defects. Herein, a model that systematically explains the observed changes in macroscopic properties of NUV LEDs is proposed. Abstract : The effect of point defects on piezoelectric field is investigated by similar‐structure near‐ultraviolet light‐emitting diodes. It is found that the piezoelectric field, the radiative recombination rate, and the redshift in peak wavelength increase with the samples' crystal quality compared with the reference sample. These optoelectronic characterizations reveal that the samples' strain relaxation is caused by defects.